Messengers in the professional communication of journalists and PR specialists in the countries of the Eurasian Economic Union - Bykov, Il'ia А.; Hradziushka, Aleksandr A.; Ibrayeva, Galiya Zh.; Turdubaeva, Elira O. (Journal of the Belarusian State University. Journalism, 2019)
The article presents the results of a study of the use of instant messengers in the professional communication of journalists and public relations specialists. The study was conducted in four countries of the Eurasian Economic Union: Belarus, Kazakhstan, Kyrgyzstan and Russia. 256 experts in journalism and PR, who have direct experience of professional communication with such applications as WhatsApp, Telegram, Facebook Messenger, Skype, Viber, etc. were interviewed. The study showed that instant messaging is becoming an important tool for journalists and public relations specialists. Most respondents believe that the most popular application for communication is Facebook Messenger. It was found out that the messengers practically replaced the usual telephone communication in the professional communications of journalists and PR specialists. The problems of the transformation of the media space of the four countries in the conditions of global digitalization are considered. Possible vectors for the evolution of the modern media environment are cited, taking into account both global factors and national specifics.
Keywords: journalism; public relations; mobile internet; messengers; internet communication; digital media